1987
DOI: 10.1002/fut.3990070402
|View full text |Cite
|
Sign up to set email alerts
|

The municipal‐treasury futures spread

Abstract: ith the debut of the municipal bond index futures contract in June of 1985, W market participants began keeping a watchful eye on the municipal-Treasury futures spread. This spread has varied widely, ranging from a low of negative eight points up to a high of plus 10% points. This has led market participants to question whether or not muni futures are being priced appropriately relative to Treasury futures.If, in fact, one market is mispriced relative to another, one can often profit from the situation by purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…For this and other reasons,a number of researchers have conducted empirical studies to determine if there are profitable trading opportunities in intercommodity spread trading. Some of these studies included: treasury bills and treasury bonds (Jones, 1981;Easterwood and Senchack, 1986), gold (Rolfo, 1981), gold and Eurodollar turtles (Poitras, 1987), gold and T-bill spreads (Monroe & Cohn, 1986), municipal bond and treasury bond (Arak, Fischer, Goodman, & Daryanani, 1987), index futures (Billingsley & Chance, 1988), soybean complex spread (Johnson, Zulauf, Irwin, & Gerlow, 1991), gold-silver spread (Wahab, Cohn, & Lashgari, 1994), spreads in agricultural futures (Barrett & Kolb, 1995) and treasury futures spreads (Park & Switzer, 1996). Monroe and Cohn (1986), for example, investigated the relative efficiency of gold futures to T-bill futures.…”
Section: Introductionmentioning
confidence: 99%
“…For this and other reasons,a number of researchers have conducted empirical studies to determine if there are profitable trading opportunities in intercommodity spread trading. Some of these studies included: treasury bills and treasury bonds (Jones, 1981;Easterwood and Senchack, 1986), gold (Rolfo, 1981), gold and Eurodollar turtles (Poitras, 1987), gold and T-bill spreads (Monroe & Cohn, 1986), municipal bond and treasury bond (Arak, Fischer, Goodman, & Daryanani, 1987), index futures (Billingsley & Chance, 1988), soybean complex spread (Johnson, Zulauf, Irwin, & Gerlow, 1991), gold-silver spread (Wahab, Cohn, & Lashgari, 1994), spreads in agricultural futures (Barrett & Kolb, 1995) and treasury futures spreads (Park & Switzer, 1996). Monroe and Cohn (1986), for example, investigated the relative efficiency of gold futures to T-bill futures.…”
Section: Introductionmentioning
confidence: 99%
“…Arak, Fischer, Goodman, and Daryanani (1987) found that using the MOB spread was an attractive trading strategy that could be made more profitable by identifying trading bounds. They identified trading bounds and the economic factors that affected the levels of the bounds.…”
Section: The Municipal Bond Futures Contractmentioning
confidence: 98%
“…Arak, Fischer, Goodman, and Daryanani (1987) developed a model of the theoretical range for the MOB spread. They found that compared with the theoretical arbitrage bounds, the original municipal futures contract was mispriced in its early months, but traded within the arbitrage bounds thereafter.…”
Section: Literature Reviewmentioning
confidence: 99%